Application of Decentralization Principle, Deconcentration Principle, and Medebewind with Impact on Public Service in East Java - Bambang Suprijadi (Jurnal Aplikasi Manajemen, 2012)
The research and observation about the balance in the application of decentralization principle, deconcentration principles and medebewind for the relationship between control and local in Indonesia research was conducted at East Java Province from April to October 2009. This research uses qualitative research methods by data collecting technique, interview and documentation of seconder data from province secretariat office, DPRD, secretariat and board of province beside that the researcher also asks opinion from the experts. The result of the researches is that the intensity of the application of decentralization principles is higher than the application of deconcentration principles in east Java, there is proper contimation on the application of this principles which gave impacto the affectivity and efficiency at the public service for society.Keywords: Decentralization, public service, society.